2012
DOI: 10.1161/circulationaha.112.121855
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Rehabilitation

Abstract: ardiac rehabilitation (CR) is a multidisciplinary, secondary prevention treatment modality 1 that reduces mortality and morbidity among patients with coronary heart disease and improves symptoms, functional capacity, metabolic status, depression, and health-related quality of life. 2,3 A recent analysis suggested that CR contributed significantly to the reduction in coronary heart disease mortality observed in the United States between 1980 and 2000 and that the risk reduction attributable to CR was comparabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Meta‐analyses suggested that CR participation can reduce all‐cause mortality by 15% to 28% for patients with MI4, 37, 38, 39 and 45% to 47% for patients with percutaneous coronary intervention 40. The effect was estimated to be comparable to improvements associated with aspirin, β‐blocker, angiotensin‐converting enzyme inhibitor, statin, and anticoagulant therapy 5, 41, 42, 43. However, the generalizability of these results was limited because the majority of trial participants were highly selected low‐risk white males, with few females, minorities, or elderly patients, and with short duration of follow‐up 4.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Meta‐analyses suggested that CR participation can reduce all‐cause mortality by 15% to 28% for patients with MI4, 37, 38, 39 and 45% to 47% for patients with percutaneous coronary intervention 40. The effect was estimated to be comparable to improvements associated with aspirin, β‐blocker, angiotensin‐converting enzyme inhibitor, statin, and anticoagulant therapy 5, 41, 42, 43. However, the generalizability of these results was limited because the majority of trial participants were highly selected low‐risk white males, with few females, minorities, or elderly patients, and with short duration of follow‐up 4.…”
Section: Discussionmentioning
confidence: 99%
“…Observational studies with long‐term mortality were sparse and mainly focused on CR participation. Prior studies lack detailed clinical and treatment information, data on severity of medical conditions, and information about other quality of care/risk interventions that patients received, which serve as important factors for CR referral and participation 4, 22, 41, 44. Most prior studies were based on claims databases that do not contain information on CR referral.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation